2021
DOI: 10.3390/nu13020547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin D Supplementation on Surrogate Markers of Fertility in PCOS Women: A Randomized Controlled Trial

Abstract: Vitamin D (VD) might play an important role in polycystic ovary syndrome (PCOS) and female fertility. However, evidence from randomized controlled trials (RCT) is sparse. We examined VD effects on anti-Müllerian hormone (AMH) and other endocrine markers in PCOS and non-PCOS women. This is a post hoc analysis of a single-center, double-blind RCT conducted between December 2011 and October 2017 at the endocrine outpatient clinic at the Medical University of Graz, Austria. We included 180 PCOS women and 150 non-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Regarding VD pretreatment (conventional medication 2000 IU-5000 IU/week, continuous medication for 2 weeks to 6 months), a total of 7 articles [ 46 52 ] were included (total number of sample cases n = 316, 9 groups of self-controlled studies) (Table S 5 ). REM analysis of 9 sets of data ( n = 316) showed that VD pretreatment (2 weeks to 6 months) in patients caused an increase in serum AMH (WMD: 0.78, 95%CI: 0.34 to 1.21; P = 0.0004) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding VD pretreatment (conventional medication 2000 IU-5000 IU/week, continuous medication for 2 weeks to 6 months), a total of 7 articles [ 46 52 ] were included (total number of sample cases n = 316, 9 groups of self-controlled studies) (Table S 5 ). REM analysis of 9 sets of data ( n = 316) showed that VD pretreatment (2 weeks to 6 months) in patients caused an increase in serum AMH (WMD: 0.78, 95%CI: 0.34 to 1.21; P = 0.0004) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples from twenty women with a diagnosis of PCOS (PCOS group) and from a further twenty women without PCOS (subfertile group) along with up to ten FF per patient were included in the analyses. PCOS was diagnosed according to the Rotterdam criteria as described [29,30], and a set of relevant clinical characteristics were determined (Table 1). At the time of sampling, 8 women in the subfertile and 15 in the PCOS group were diagnosed as primary infertile.…”
Section: Study Populationmentioning
confidence: 99%
“…A study by Samantha F Butts et al found that ovulation and live birth rates were 15.2% and 40% lower, respectively, in VD deficient PCOS patients than in normal women [114]. Recent studies have shown that VD supplementation can increase FSH levels in PCOS patients, thereby decreasing LH/FSH values, and improving IR and hyperlipidemia, thus increasing ovulation and pregnancy rates in PCOS patients [115,116]. Severe OS is one of the causes of PCOS.…”
Section: Clinical Observation and Mechanism Of Supplementingmentioning
confidence: 99%